Rehabilitation of Grindelia argentina (Asteraceae: Astereae) and updates on its geographic range - Deble, Leonardo Paz; Sabatino, Malena (Balduinia, 2023)
Rehabilitation of Grindelia argentina (Asteraceae: Astereae) and updates on its geographic range. Grindelia argentina is rehabilitated from the synonymy of G. buphthalmoides and comments about morphology and related taxa are mentioned. Further, the existence of G. argentina in the orographic Tandilia System is confirmed, which increase the geographic distribution of this species.